Ranching Women in Southern Alberta - Herbert, Rachel (University of Calgary Press, 2017)
Settler ranching in southern Alberta conjures the image of a lone cowboy riding through the foothills or a stoic ranch hand roping errant cattle. But women have always played an integral part in the cattle industry, often working without recognition or support to meet the challenge of the frontier. Ranching Women in Southern Alberta examines the rhythms, routines, and realities of women's lives on family ranches. As these ranches replaced the large-scale cattle operations that once covered thousands of acres, women were called upon to ensure not only the ongoing economic viability of their ranches, but also the social harmony of their families and communities. At the same time, ranching women enjoyed personal freedoms and opportunities unknown to their urban and European contemporaries. The great-granddaughter of pioneer ranchers, Rachel Herbert brings a unique insight to the stories of these brave and talented women who carved a role for themselves and their daughters during the dawn of the family ranch.